Impactul voluntariatului in activitatea bibliotecii publice - GOIAN, Natalia; MANOILOVA, Liliana (BIBLIOPOLIS, 2026)
The article aligns with other initiatives aimed at investigating the necessity of volunteer activity in libraries. It analyzes the importance of volunteering in libraries, highlighting its benefits for young volunteers, libraries, and society as a whole. Volunteering contributes to the personal development of young people, increases social and cultural capital, and improves library services. At the same time, the article discusses challenges such as the risk of volunteer work becoming monotonous, emphasizing the need for activities to be meaningful and supportive of the educational process for the young individuals involved.